Beyond the Halal-Haram Dichotomy: Reconstructing Islamic Legal Reasoning on Crypto Asset Trading through Ta'aqquli and the Principle of Dar'u al-Mafasid Muqaddam 'Ala Jalbi al-Masalih - M. Wahab Syakrani; M. Haitami; Muliana; M. Taufikkurrahman; Noraslina binti Sulaiman (NALAR FIQH: Jurnal Hukum Islam, 2025)
The legal status of crypto asset trading remains a debated issue in contemporary Islamic law. Most previous studies assess the issue through a simple halal or haram framework, which does not fully capture the complexity of Islamic legal reasoning. This study examines the legal assessment of crypto asset trading by combining ta'aqquli reasoning with the legal maxim dar'u al-mafasid muqaddam 'ala jalbi al-masalih within the broader objectives of maqasid al-shari'ah. The research uses a qualitative library approach based on normative and conceptual analysis. The data consist of classical and contemporary Islamic legal literature, fatwas, government regulations, and academic publications on cryptocurrency and Islamic finance. The study applies qualitative content analysis and comparative legal analysis to identify the legal basis of crypto asset transactions, assess the balance between potential benefits and harms, and develop a more systematic framework for legal evaluation. The findings show that crypto asset trading falls within the scope of ta'aqquli, where legal rulings should consider rational legal causes, governance standards, regulatory oversight, asset utility, and public interest. Therefore, the principle of preventing harm should function as a framework for balanced evaluation rather than as an automatic reason to prohibit all crypto asset trading. Based on these findings, this study proposes the Ta'aqquli-Maslahah Gradation Model, which classifies crypto assets into three legal categories according to the balance between potential benefits and harms. The model uses practical indicators, including asset characteristics, underlying value, Sharia compliance, governance quality, regulatory status, investor protection, market stability, and consistency with the objectives of Islamic law. This model offers a practical framework for evaluating digital financial innovation and provides guidance for fatwa institutions, regulators, and Muslim investors in assessing crypto assets through a contextual and evidence-based Sharia perspective.